Highly Stable and Photoluminescent CsPbBr3/Cs4PbBr6 Composites for White-Light-Emitting Diodes and Visible Light Communication - Longshi Rao; Bin Sun; Yang Liu; Guisheng Zhong; Mingfu Wen; Jiayang Zhang; Ting Fu; Shuangxi Wang; Fengtao Wang; Xiaodong Niu (Nanomaterials, 2023)
Inorganic lead halide perovskite is one of the most excellent fluorescent materials, and it plays an essential role in high-definition display and visible light communication (VLC). Its photochromic properties and stability determine the final performance of light-emitting devices. However, efficiently synthesizing perovskite with high quality and stability remains a significant challenge. Here, we develop a facile and environmentally friendly method for preparing high-stability and strong-emission CsPbBr3/Cs4PbBr6 composites using ultrasonication and liquid paraffin. Tuning the contents of liquid paraffin, bright-emission CsPbBr3/Cs4PbBr6 composite powders with a maximum PLQY of 74% were achieved. Thanks to the protection of the Cs4PbBr6 matrix and liquid paraffin, the photostability, thermostability, and polar solvent stability of CsPbBr3/Cs4PbBr6-LP are significantly improved compared to CsPbBr3 quantum dots and CsPbBr3/Cs4PbBr6 composites that were prepared without liquid paraffin. Moreover, the fabricated CsPbBr3/Cs4PbBr6-LP-based WLEDs show excellent luminescent performance with a power efficiency of 129.5 lm/W and a wide color gamut, with 121% of the NTSC and 94% of the Rec. 2020, demonstrating a promising candidate for displays. In addition, the CsPbBr3/Cs4PbBr6-LP-based WLEDs were also demonstrated in a VLC system. The results suggested the great potential of these high-performance WLEDs as an excitation light source to achieve VLC.